LINGUISTIC ASPECTS OF THE DEVELOPMENT OF COMPUTER SIGN LANGUAGE INTERPRETERS RUSSIAN LANGUAGE - Natalia Davidovna Ganelina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
The article is devoted to the actual direction of modern linguistics – describing the features of Russian sign language identified by the analysis of theoretical and empirical lexicographical sources, as well as in the process of communication with native «speakers» – people using Russian sign language as native language. Another purpose of the article is detecting and confirming the practical significance of such research – solving problems of social adaptation for hard of hearing people. The paper presents the results of linguistic research of Russian sign language that the developers of the computer Russian sign language translator rely on: peculiarities of lexis, word derivation, morphology and syntax of sign language for deaf citizens of the Russian Federation are described. Approaches to developing a system for computer sign language translation used by the employees of the Institute of Social Rehabilitation, Novosibirsk State Technical University, are justified in the paper. The results of the research can be interested to specialists studying and describing lexical and grammatical systems of Russian sign language, developers of the system for a two-way machine translation from Russian spoken language to Russian sign language and vice versa, sign language interpreters and teachers of sign language. DOI: http://dx.doi.org/10.12731/2218-7405-2013-7-28